Implementasi Kebijakan Pengelolaan Sampah Di Kecamatan Wanea Kota Manado - Valery Manoppo; VERY LONDA; ALDEN LALOMA (JURNAL ADMINISTRASI PUBLIK, 2022)
: Design This study is being used in a descriptive method derives Researchers want to describe give elaborate on how the implementation of waste management policy in East kecamatan wanea District Government of the State, with the face of data collection is done by interview give documentation. This is Reported in Research ViceÂ Â  give subdistrict head wanea, Head 5 (five), Head 4 (empathy) give the Community. Results showed realization give waste management program in kecamatan wanea State in 2014 in 4 (empathy) District of running properly, Environmental cleanliness program's budget from the central government, namely the Ministry of Internal Affairs of Manado City. Implementation of policy initiatives dominated give more initiative from the Central Government (Top Down). wanea district Government, giving it more community empowerment practicing general education as well as specialized as well as an evaluation of the implementation of the policy of the Government in the implementation of the waste management program. Then, in order to obtain the existence of political support from all elements of society and the social party political.